2021
DOI: 10.1002/hep.31537
|View full text |Cite
|
Sign up to set email alerts
|

Gallstones, Body Mass Index, C‐Reactive Protein, and Gallbladder Cancer: Mendelian Randomization Analysis of Chilean and European Genotype Data

Abstract: Background & aims: Gallbladder cancer (GBC) is a neglected disease with substantial geographical variability: Chile shows the highest incidence worldwide, while GBC is relatively rare in Europe. Here we investigate the causal effects of risk factors considered in current GBC prevention programmes as well as C-reactive protein (CRP) level as a marker of chronic inflammation. Approach & results: We applied two-sample Mendelian randomization (MR) using publicly available data and our own data from a retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 58 publications
4
45
0
Order By: Relevance
“…The number of MR studies based on independent study samples for each disease category was two for diabetes mellitus [ 7 , 8 ], 13 for circulatory system diseases [ 9 – 21 ], three for respiratory diseases [ 8 , 22 , 23 ], six for digestive system diseases [ 24 29 ], five for musculoskeletal system diseases [ 30 34 ] plus FinnGen consortium (for osteoporosis), five for nervous system diseases [ 35 39 ], and 14 for neoplasms [ 40 – 53 ]. Among the selected studies, six studies included East-Asian (Chinese [ 11 , 25 , 42 ] and Japanese [ 48 , 50 ]) or Chilean [ 53 ] individuals, whereas the remaining studies included individuals of European ancestry or mixed (trans-ancestry) populations. Details and results of published MR studies included in the meta-analyses as well as results from de novo MR analyses of FinnGen data are provided in Additional file 1 : Table S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of MR studies based on independent study samples for each disease category was two for diabetes mellitus [ 7 , 8 ], 13 for circulatory system diseases [ 9 – 21 ], three for respiratory diseases [ 8 , 22 , 23 ], six for digestive system diseases [ 24 29 ], five for musculoskeletal system diseases [ 30 34 ] plus FinnGen consortium (for osteoporosis), five for nervous system diseases [ 35 39 ], and 14 for neoplasms [ 40 – 53 ]. Among the selected studies, six studies included East-Asian (Chinese [ 11 , 25 , 42 ] and Japanese [ 48 , 50 ]) or Chilean [ 53 ] individuals, whereas the remaining studies included individuals of European ancestry or mixed (trans-ancestry) populations. Details and results of published MR studies included in the meta-analyses as well as results from de novo MR analyses of FinnGen data are provided in Additional file 1 : Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…These observational findings [ 1 6 ] may represent the causal effect of obesity on disease risk or confounding from other risk factors, such as a poor diet and physical inactivity. During the last years, an increasing number of Mendelian randomization (MR) studies of adiposity, mostly defined by body mass index (BMI), in relation to chronic diseases have been published [ 7 53 ]. MR is an instrumental variable analysis that exploits genetic variants with a robust impact on the exposure (e.g., BMI) as proxy markers for the exposure to test whether the exposure has a causal relationship with disease risk [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transferrin saturation showed increased risk of liver cancer, but transferrin levels presented a decreased risk [ 311 ]. The rest of the robust associations pertained to age at menarche with ovarian (total and serous; decreased risk) [ 260 ], alcohol use disorder diagnostic codes with ovarian serous (decreased risk) [ 317 ], endometriosis with ovarian [ 261 ] and with endometriosis-uterine leiomyoma [ 235 ] (both increased risk), gallstone disease with gallbladder (increased risk) [ 264 ], insulin-like growth factor 1 (IGF-1) with breast (increased risk) [ 295 ], obstructive sleep apnea syndrome with breast (increased risk) [ 271 ], polycystic ovary syndrome with ovarian endometrioid (decreased risk) [ 237 ], stem cell growth factor beta (SCGF-β) with prostate (decreased risk) [ 304 ], schizophrenia with breast (total, ER+, ER−; increased risk) [ 210 ], standardized forced expiratory volume in 1 s with lung SCC (increased risk) [ 281 ], thyroid-stimulating hormone with cancer overall (decreased risk) [ 313 ], type 2 diabetes with esophageal (decreased risk) [ 312 ], and vitiligo with non-melanoma skin, melanoma, and ovarian (decreased risk) [ 306 ].…”
Section: Resultsmentioning
confidence: 99%
“…65 Obesity is associated with increased bile acid (BA) synthesis, which provokes supersaturation of BA in the gallbladder and subsequently gallstone formation (cholelithiasis). [66][67][68] Cholecystitis, an inflammation of the gallbladder most often developed by a gallstone, 68,69 was causally associated with increased adiposity along with cholelithiasis in our results (Figures 2 and 3). The result was in concordance with a previous MR-based phenomewide association study that reported the causal effect of BMI on cholecystitis.…”
Section: Discussionmentioning
confidence: 64%